Structural and Functional Analysis of Crucial Protein Complex in Basal Cell Skin Carcinoma via Network Construction - Zamanian Azodi, Mona; Rezaei-Tavirani, Mostafa; Rezaei-Tavirani, Majid; Rostami-Nejad, Mohammad (Galen Medical Journal, 2019)
Â Background: The basal-cell carcinoma (BCC) as one of the most common type of skin cancers reported to have an increasing trend during past years. Molecular approaches can be useful to advance diagnosis and treatment goals in this cancer.Materials and Methods: In this sense, one of the recent popular investigations, protein-protein interaction network analysis (PPI), wasÂ applied in this study to better facilitate molecular view of BCC. Â Cytoscape v3.6.0 and its plug-ins analyzed and explored the topological and annotation features of the constructed network.Â Result: Among TP53, EGFR, AKT1, ERBB2, HRAS, and CCND1 as central agents of the network, five of them were also present in the first prominent cluster of the network in which considered for further analysis. It is suggested that there are significant related biological processes, actions, and expression changes for this highlighted cluster that may be related to BCC risk.Â Â Conclusion: Therefore, the studied complex of proteins may worth considering for clinical studies and therapeutic interventions after validating by related tests. What is more, among these genes, EBBR2 has more to offer and consequently with additional values. Â [GMJ.2018;7:e1271]